Case Study on Instrumenting and Testing Full-Scale Test Piles for Evaluating Setup Phenomenon. Issue 1 (January 2014) - Haque, M. Nafiul; Abu-Farsakh, Murad Y.; Chen, Qiming; Zhang, Zhongjie
Over time, piles driven in cohesive soils usually experience a large increase in resistance, known as setup or freeze. Dynamic load tests (DLT) and static load tests (SLT) are usually performed to verify the axial resistances of piles at specific times after end of driving (EOD) and to quantify these resistances. An extensive field testing program was performed on full-scale instrumented precast prestressed concrete piles driven in cohesive soils at the Bayou Lacassine Bridge in Louisiana, to evaluate the pile setup phenomenon. The testing program included instrumenting two full-scale test piles with a network of vibrating wire strain gauges, pressure cells, and piezometers and instrumenting the surrounding soils with multilevel piezometers. Five SLTs and three DLTs were conducted on each test pile at different times after EOD to quantify the magnitude of setup. Measurements from the load tests on both piles confirmed that the pile setup after EOD followed a logarithmic rate with time. An increase in piles' total resistances (or setup) of 1.60 to 1.77 times the EOD resistances was observed after the final restrikes. Piezometer data demonstrated a close relationship between the dissipation of excess pore water pressures that were generated during pile driving, following EOD, and pile setup. The load transfer curves derived from the strain gauge measurements were used to separate the side and tip resistance profiles from the total resistance. Piezometers installed in the ground showed that the influence zone, caused by pile driving, extends beyond the 3B distance (B = pile width).